How Batman saved the classroom - van der Krogt S; Green J; Manning C; Burrow M (New Zealand Nurses Organisation)
2020 was one of the most exceptional teaching years we have experienced. The pandemic and public health response severely disrupted all clinically-based teaching institutions around the world. Nursing schools everywhere were required to rapidly pivot their courses online to limit the disruption to teaching. This article highlights elements that can successfully engage nursing students in online learning. There is minimal literature discussing the need for a holistic teaching design that promotes a nonthreatening, learning environment and which encourages the free exchange of ideas and questions normally associated with face-to-face teaching. The online learning programme we designed at Massey University incorporates humour, game-based learning and consideration of students’ wellness. We believe this will be of interest to our nursing colleagues, as well as those in other professions.
Keywords: 1110 Nursing